Viscoelastic Properties of Differentiating Blood Cells Are Fate- and Function-Dependent - Ekpenyong, Andrew E.; Whyte, Graeme; Chalut, Kevin; Pagliara, Stefano; Lautenschlaeger, Franziska; Fiddler, Christine; Paschke, Stephan; Keyser, Ulrich F.; Chilvers, Edwin R.; Guck, Jochen (PLoS ONE, 2012)
Although cellular mechanical properties are known to alter during stem cell differentiation, understanding of the functional relevance of such alterations is incomplete. Here, we show that during the course of differentiation of human myeloid precursor cells into three different lineages, the cells alter their viscoelastic properties, measured using an optical stretcher, to suit their ultimate fate and function. Myeloid cells circulating in blood have to be advected through constrictions in blood vessels, engendering the need for compliance at short time-scales (<seconds). Intriguingly, only the two circulating myeloid cell types have increased short time scale compliance and flow better through microfluidic constrictions. Moreover, all three differentiated cell types reduce their steady-state viscosity by more than 50% and show over 140% relative increase in their ability to migrate through tissue-like pores at long time-scales (>minutes), compared to undifferentiated cells. These findings suggest that reduction in steady-state viscosity is a physiological adaptation for enhanced migration through tissues. Our results indicate that the material properties of cells define their function, can be used as a cell differentiation marker and could serve as target for novel therapies. © 2012 Ekpenyong et al.
CRIS-Team Scopus Importer:2022-08-05